(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In recent years, the development of portable and Internet of Things (IoT) technologies has revolutionized the way we monitor and control various systems remotely. It describes physical items that have sensors and actuators built in that may connect to computing systems across wired or wireless networks to monitor or even control the physical environment. The multi-task portable IoT-based remote control vehicle for area monitoring using Arduino Uno R3 with alarm, night vision, and heat sensors is an innovation of these electronics mechanisms that integrates several sensors and Arduino Uno R3 as the microcontroller. The Prototype contains a night vision camera for low-light conditions, an alarm that is intended to alert a specific person or group of individuals and a heat sensor that provides an efficient yet inexpensive way to measure temperature and humidity. The proposed system can be remotely controlled through a mobile app-based user interface, allowing users to monitor an area in real time and detect potential security threats. According to the strategy that was described, this chapter gives specific findings. It provides information on the prototype’s hardware and software as well as the results of tests conducted on the multi-task portable IoT-based remote control vehicle for area monitoring using Arduino Uno R3 with alarm, night vision, and heat sensors. After testing, researchers found that the sensor components used were compatible with Arduino Uno R3 to read data and send information to NodeMCU ESP8266 using serial communication between the two of them. The NodeMCU and ESP32 Camera can connect to the internet, display some information on the Blynk Application, and control the vehicle.